The Effectiveness of Denture Cleansers on Soft Denture Liners Colored by Food Colorant Solutions - Duygu Sara¸c, DDS, PhD;1 Y. S¸inasi Sara¸c, DDS, PhD;1 (Journal of Prosthodontics, 2007)
The aim of this study was to investigate the color stability of soft denture liners and the effectiveness of denture cleansers on soft denture liners colored by food colorants in different time periods